Respuesta :
1.
3x - y = - 6
6 + 3x = y
y = 3x + 6
2.
x - 3y = 3
-3 + x = 3y
3y = x - 3
y = 1/3(x-3)
y = x/3 - 1
3.
9x + 3y = 6
3y = -9x + 6
y = 1/3(-9x + 6)
y = -3x + 2
4.
x + 3y = -6
3y = -x - 6
y = 1/3(-x - 6)
y = -x/3 - 2
3x - y = - 6
6 + 3x = y
y = 3x + 6
2.
x - 3y = 3
-3 + x = 3y
3y = x - 3
y = 1/3(x-3)
y = x/3 - 1
3.
9x + 3y = 6
3y = -9x + 6
y = 1/3(-9x + 6)
y = -3x + 2
4.
x + 3y = -6
3y = -x - 6
y = 1/3(-x - 6)
y = -x/3 - 2
So the problem want to ask to convert the following equation in to a slope intercept form and the formula of it is y = mx+b and the answers are the following:
#1. y = 3x+6
#2. y = x/3-1
#3. y = -3x+2
#4. y = -x/3 - 2
I hope you are satisfied with my answer and feel free to ask for more if you have questions and further clarifications. Have a nice day
#1. y = 3x+6
#2. y = x/3-1
#3. y = -3x+2
#4. y = -x/3 - 2
I hope you are satisfied with my answer and feel free to ask for more if you have questions and further clarifications. Have a nice day